2012
DOI: 10.1016/j.vaccine.2011.12.134
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lassa virus vaccine immunogenicity in a CBA/J-ML29 mouse model

Abstract: Lassa fever (LF) is one of the most prevalent viral hemorrhagic fevers in West Africa responsible for thousands of deaths annually. The BSL-4 containment requirement and lack of small animal model to evaluate Lassa virus (LASV)-specific cell-mediated immunity (CMI) complicate development of effective LF vaccines. Here we have described a CBA/J-ML29 model allowing evaluation of LASV-specific CMI responses in mice. This model is based on Mopeia virus reassortant clone ML29, an attractive immunogenic surrogate fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 46 publications
5
53
0
1
Order By: Relevance
“…These studies have shown that use of NP, GPC or the 2 G proteins or a combination of NP/GPC is protective in a variety of animal models. 10,14,15,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Studies of convalescent sera from patients with Lassa Fever or human HLA transgenic mice identified a number of epitope targets within the NP, GP1, GP2 and GS proteins. 11,12,16,19,[57][58][59][60][61][62][63] Recent work in a guinea pig model utilizing the GP1 and GP2 proteins in a DNA vaccine resulted in adequate protection from challenge virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have shown that use of NP, GPC or the 2 G proteins or a combination of NP/GPC is protective in a variety of animal models. 10,14,15,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Studies of convalescent sera from patients with Lassa Fever or human HLA transgenic mice identified a number of epitope targets within the NP, GP1, GP2 and GS proteins. 11,12,16,19,[57][58][59][60][61][62][63] Recent work in a guinea pig model utilizing the GP1 and GP2 proteins in a DNA vaccine resulted in adequate protection from challenge virus.…”
Section: Discussionmentioning
confidence: 99%
“…19,[65][66][67] The ML29 reassortment virus vaccine, comprising the L and Z protein from Mopeia virus-an Old World arenavirus closely related to Lassa-and the GPC and NP proteins from Lassa, have also been effective in a number of vaccine studies. 20,47,50,51,55 The L protein of Mopeia was chosen to serve as a replication or translational attenuation factor in the vaccine. We therefore limited the peptide targets to class I and class II peptides of the Lassa glycoproteins G1 and G2.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of misfolded GP in the lumen of ER triggered the UPR (unfolded protein response) and apoptosis promoting cross-presentation. Bivalent VLPVs simultaneously expressing modified LASV " GPfib and wild-type GPs from lineages I and IV completely protected mice against fatal challenge [131] and induced cross-reactive cell-mediated immune responses against all LASV lineages currently circulated in West Africa. Notably, these VLPVs also induced population of CD11c+CD8±+ cells involved in cross-presentation pathway (Fig.…”
Section: Other Recombinant-competent Lasv Vaccine Platforms Tested Inmentioning
confidence: 99%
“…PerCP-cy5.5, CD8a-APC, CD11b-APC, CD11c-Alexa Fluor 488, and analyzed by flow cytometry ([115,131] with authors' modifications; Lukashevich & Pushko, unpublished). Downloaded by [RMIT University Library] at 02:03 19 May 2016 Downloaded by [RMIT University Library] at 02:03 19 May 2016…”
mentioning
confidence: 99%
“…Several studies have been used to identify the protective capacity of this reassortant virus on LASV challenges [84,85,87,91]. ML-29 is capable of protecting against several strains of LASV, and shows potential to have some cross-protective tendencies for LCMV-WE [87].…”
Section: Future Directionsmentioning
confidence: 99%